2022
DOI: 10.3390/molecules27041250
|View full text |Cite
|
Sign up to set email alerts
|

Pickering Emulsions Stabilized with Curcumin-Based Solid Dispersion Particles as Mayonnaise-like Food Sauce Alternatives

Abstract: Pickering emulsions, which are emulsions stabilized by colloidal particles, are being increasingly positioned as novel strategies to develop innovative food product solutions. In this context, the present work aims to develop Pickering emulsions stabilized by natural-based curcumin-loaded particles produced by the solid dispersion technique as promising mayonnaise-like food sauce alternatives. Two particle formulations (KC1 and KC2) were produced using k-carrageenan as the matrix material and different curcumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 41 publications
(53 reference statements)
3
1
0
Order By: Relevance
“…In this study, all treated samples showed increased work of cohesion compared to the untreated one, however, there is no significant difference ( p > 0.05). The sample obtained after ultrasonication as a pre‐treatment showed the highest value of work of cohesion which is in agreement with the results reported by Ghirro et al (2022). This is attributed to the significant droplet size reduction during sonication.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, all treated samples showed increased work of cohesion compared to the untreated one, however, there is no significant difference ( p > 0.05). The sample obtained after ultrasonication as a pre‐treatment showed the highest value of work of cohesion which is in agreement with the results reported by Ghirro et al (2022). This is attributed to the significant droplet size reduction during sonication.…”
Section: Resultssupporting
confidence: 92%
“…In another work, a yogurt prepared from US buffalo milk also showed nearly 98% higher hardness as compared to that prepared from untreated milk owing to the same reason (Abesinghe et al, 2020). On agreement with the results reported by Ghirro et al (2022). This is attributed to the significant droplet size reduction during sonication.…”
Section: Textural Analysissupporting
confidence: 82%
“…This phenomenon may apply for the case of the control sauces; the increased fat droplet size resulted in lower particle concentration and in a higher fraction of fat volume, thus less stable formulation during storage as seen in Figure 10. These observations are consistent with previously reported studies [58][59][60]. The results were also confirmed by the accelerated emulsion stability test that was conducted at zero time by centrifugation.…”
Section: Shelf-life Determination Of New White Saucessupporting
confidence: 93%
“…In this case, the solid particles were used as an alternative to egg yolk and contributed to developing disruptive products with vegan characteristics. In this context, Lu et al [ 164 ], Akcicek et al [ 165 ], Ghirro et al [ 166 ] and Li et al [ 167 ] studied the possibility of using PEs stabilised by apple pomace particles, gum nanoparticles, curcumin-based solid dispersion particles and pea protein isolate microgels, respectively, for the development of edible mayonnaises. The stability of the emulsions during storage and against different environmental stresses and rheological properties was studied to validate the use of solid particles.…”
Section: Pickering Emulsions For Food Applicationsmentioning
confidence: 99%